2018
DOI: 10.1371/journal.pone.0207017
|View full text |Cite
|
Sign up to set email alerts
|

Public knowledge and perception about antimicrobials and antimicrobial resistance in Japan: A national questionnaire survey in 2017

Abstract: BackgroundAntimicrobial resistance (AMR) is a threat to global health. To increase public awareness about AMR and encourage the prudent use of antimicrobials is one of the goals of the National Action Plan in Japan.MethodsA nationwide online cross-sectional survey was conducted to evaluate the existing knowledge and perception of AMR in Japan, based on the Antimicrobial Resistance Eurobarometer Survey. Participants included Japanese adults aged 20–69 years, who were not medical professionals.ResultsAmong a tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
43
2
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 11 publications
8
43
2
4
Order By: Relevance
“…23,29 No que concerne o acesso ao AB, dois estudos, na Suécia (n=747) e no Japão (n=3.390), demonstraram, respetivamente, que 7,6% e 11,7% dos utentes admitem guardar excedente de AB em casa. 21,30 Porém, o valor encontrado (90,7%) é claramente superior e assemelha-se veterinário e 23,5% a criação de novos AB. Na questão 14, 64,2% dos doentes afirmou que a RAB resulta do uso incorreto do AB e 42,0% revelou que o AB utilizado de forma desnecessária numa determinada região pode ser prejudicial para os seus residentes.…”
Section: Resultsunclassified
See 3 more Smart Citations
“…23,29 No que concerne o acesso ao AB, dois estudos, na Suécia (n=747) e no Japão (n=3.390), demonstraram, respetivamente, que 7,6% e 11,7% dos utentes admitem guardar excedente de AB em casa. 21,30 Porém, o valor encontrado (90,7%) é claramente superior e assemelha-se veterinário e 23,5% a criação de novos AB. Na questão 14, 64,2% dos doentes afirmou que a RAB resulta do uso incorreto do AB e 42,0% revelou que o AB utilizado de forma desnecessária numa determinada região pode ser prejudicial para os seus residentes.…”
Section: Resultsunclassified
“…38 Existe uma «necessidade» de prescrição com AB por parte do doente sendo que, no Qatar, 28,1% espera tratamento com ATB 23 e, no Japão, 10,2% formaliza um pedido por consulta. 30 Um estudo transversal na Holanda, com 935 participantes, obteve resultados semelhantes. Cerca de 37% admitem capacidade de suspeição para tratamento com AB e 92,9% acreditam que a decisão de iniciar AB deve ser tomada pelo médico, valores inferiores aos encontrados, 50,4% e 95,7%, respetivamente.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…To control antimicrobial-resistant bacteria, it is necessary to encourage public understanding of the threat of AMR and to change the way antibiotics are handled. Concerning public awareness of AMR, an awareness survey of 3,390 people in Japan was conducted (6). The results of the survey indicated that 46.8% and 40.6% of respondents, respectively, believed that the following statements were correct: "antibiotics kill viruses" and "antibiotics are effective against the common cold and influenza", while 38.8% of all respondents were aware that antibiotics may cause adverse reactions.…”
Section: Knowledge Awareness and Attitude Of The Public Towards Amrmentioning
confidence: 99%